1978
DOI: 10.1136/bmj.2.6150.1453
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity in men one week after first acute myocardial infarction.

Abstract: Summary and conclusionsOne week after a first myocardial infarction 35 out of 100 consecutive men patients aged under 65 were found by standardised clinical interview to have psychiatric morbidity. In 16 the morbidity had been evident before the infarct, and these patients showed a wider range of psychopathology than those whose symptoms had been precipitated by the infarct.The results suggest that psychiatric morbidity in patients with heart disease is not necessarily a result of the disease process. Thus cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 6 publications
1
30
0
Order By: Relevance
“…The majority of the studies analyzed depressive disorders (N = 10) [12,13,[20][21][22][23]26,27,30,31], followed by anxiety disorders (N = 3) [13,20,30]. Three studies investigated any mental disorder not further specified [24,28,29]. Comorbid mental disorders were assessed by clinical interviews (N = 3) [13,21,28] and screening questionnaires (N = 9) [12,20,22,23,24,26,[29][30][31].…”
Section: Data Abstractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies analyzed depressive disorders (N = 10) [12,13,[20][21][22][23]26,27,30,31], followed by anxiety disorders (N = 3) [13,20,30]. Three studies investigated any mental disorder not further specified [24,28,29]. Comorbid mental disorders were assessed by clinical interviews (N = 3) [13,21,28] and screening questionnaires (N = 9) [12,20,22,23,24,26,[29][30][31].…”
Section: Data Abstractionmentioning
confidence: 99%
“…Three studies investigated any mental disorder not further specified [24,28,29]. Comorbid mental disorders were assessed by clinical interviews (N = 3) [13,21,28] and screening questionnaires (N = 9) [12,20,22,23,24,26,[29][30][31]. Ladwig et al (1994) [27] did not describe the assessment of comorbid mental disorders.…”
Section: Data Abstractionmentioning
confidence: 99%
“…Twenty-one of the 24 patients studied rated themselves as anxious or depressed, 18 were assessed to require either a sedative or an antidepressant, 15 reported sleep distur bances, and 18 reported disruptive family quarrels. Another study found 33% of a sam ple of postmyocardial infarction patients ex 153 hibited signs of severe depression as much as 18 months after infarction [54], In addition, two groups have reported that at least half of their sample of patients describing psychiatric symptoms after their myocardial infarction had described experiencing similar symptoms predating the infarction [53,57], Drawing conclusions from studies investi gating the association between psychiatric and depressive symptomatology and coronary artery disease has been limited by the various criteria and methods used to define both psy chiatric morbidity and depressive symptoms. These diverse methods include self-report, clinical diagnosis, and symptom checklist.…”
Section: Depression and Heart Diseasementioning
confidence: 99%
“…Between 20 and 40% of patients with coronary artery disease have been found to exhibit depressive symptoms [51][52][53][54][55][56][57]. Wishnie [57] studied psychiatric symptomatology in 24 patients in the early phase of their recov ery. Twenty-one of the 24 patients studied rated themselves as anxious or depressed, 18 were assessed to require either a sedative or an antidepressant, 15 reported sleep distur bances, and 18 reported disruptive family quarrels.…”
Section: Depression and Heart Diseasementioning
confidence: 99%
“…Other investigators found nonsuicidal deaths and myocardial infarc tion to be significantly more frequent in un treated depressed patients compared to an adequately treated group [6], Murphy and Brown [111] found that the link between severe life events and the onset of physical illness, for women of 50 years or younger, was not a direct causal association, but was mediated by a depressive disorder. For ex ample, almost half of the patients showing a depressive disorder after their first myocar dial infarction had suffered from depression prior to the infarct [100].…”
mentioning
confidence: 99%